The Role of Kewang Customary Institution as a Biosecurity Strategy of Community Livelihood Asset in Negeri Booi - Hahury, Hendri Dony; Prabawa, Tity Susilowati; Giloso, Pamerdi Wiri; Soumokil, Tontji; Ndoen, Marthen Luther (Departement of Communication and Community Development Sciences, Faculty of Human Ecology, 2019)
Population growth which is not supported with the availability of natural resources causes gaps or limitations in meeting daily needs through natural resources. As a result, rural communities need certain rules or norms used as behavioral guidelines in utilizing the natural resources. One of them is through the existence of kewang customary institution. However, as the community develops, its effectiveness is experiencing a decline. This study examines the role of kewang customary institution as a biosecurity strategy for community livelihood asset in Negeri Booi, Saparua Island, Central Maluku Regency. This study was done in a qualitative manner with a case study method. The key informants involved included members of the kewang, head (raja) of Negeri Booi, farmers and customary leaders. In-depth interviews, observation and focus group discussion (FGD) were used to collect the data. The results showed that the kewang of Negeri Booi played an active role in securing the livelihood asset while at the same time protecting Negeri Booi's territory. However, the inclusion of economic interventions left the kewang members vulnerable. They were faced with the choice to carry out their duties and functions as a local institution securing the livelihood asset or to violate the convention to meet their daily household needs. In general, the community in Negeri Booi still recognized the existence of kewang customary institution by respecting and carrying out every decision taken.